Pengaruh Total Persediaan, Total Aktiva dan Total Modal terhadap Laba Bersih pada Sub Sektor Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2012-2016 - Hana Tamara Putri (Ekonomis: Journal of Economics and Business, 2018)
The purpose of this research is to know the influence of the total inventory, total assets and total working capital simultaneosly and partially to net profit on subsector of property and real estates on period 2012-2016. This research is a desciptive quantitative research and analysis tool used in this research are multiple linear regression is useful to see the direction of the relationship between the variable-variable bound against free. For the purpose of answering the number one used statistical test i.e test F and to answer the purpose number 2 used statistical test i.e test t. The correlation coefficient to know how the relationship between variables and coefficients of determination of useful to see the magnitude of the influence of the variable bound against free. Result SPSS 20 get a multiple linear regression equation is Log Y = 4-0,103 + 0,156 X1 + 0,748 X2 – 0,049 X3 + e. The corellation is 0,774, meaning that is a close relationship between the variable total inventory (X1), total assets (X2) and working capital (X3) of net profit (Y) on sub sector of property and real estate on period 2012-2016. From the result of the obtained values SPSS (coefficient) r2 this figure amounted 59,9% states that the variable total inventory, total assets and working capital of the able to explain the variabel net profit by 59,9% and the reaining 40,1% is explained by other factors which is not included in the research model. Simultaneously the total inventory, total assets and working capital of a significant effect on net profit on sub sector of property and real estate on period 2012-016 and partially total inventory has no influence on net profit and working capital total asset has an influence on net profit on sub sector of property and real estate on period 2012-2016